Nutritional plasticity and evolutionary divergence in the Drosophila ovary - Mendes, Cláudia Carolina de Almeida (2018)
The environment can modify developmental trajectories and generate a range of distinct phenotypes without altering an organism’s genome, a widespread phenomenon called developmental plasticity. The past decades have seen a resurgent interest in understanding how developmental plasticity contributes to evolutionary processes, as it can produce phenotypic variation among individuals and facilitate diversification among populations that inhabit distinct ecological niches. To better understand the importance of plastic responses for evolutionary change, we need to explore how the environment alters development to produce phenotypic variation and then compare this to how genetic variation influences these same developmental processes.(...)